Empathy or Empathies? Uncertainties in the Interdisciplinary Discussion - Pinotti Andrea; Salgaro Massimo (Gestalt Theory, 2019)
The term empathy has become a linguistic commonplace in everyday communication as well as in interdisciplinary research. The results of the research questions, raised in the last hundred (and more) years, coming from different areas, such as aesthetics, psychology, neurosciences and literary theory, lack in fact a clear concept of empathy. Not surprisingly, a recent paper has identified up to 43 distinct definitions of empathy in academic publications. By reconstructing the main research lines on empathy, our paper highlights the reasons for this conceptual inadequacy and the deficiencies in the theorization of empathy that create misleading interpretations thereof. Along the line connecting Plato’s insights on empathic experiences to the present neuroscientific experiments, a broad spectrum of issues is deployed for which “empathy” functions as an umbrella term covering a net of categorical relationships – projection, transfer, association, expression, animation, anthropomorphization, vivification, fusion, and sympathy – that only partially overlap. Our paper therefore recommends that “empathy” should not be assumed as a self-evident notion but instead preliminarily clarified in its definition every time we decide to have recourse to it.